Application of Model Problem Based Learning Assisted Blended Learning on Cognitive Knowledge of University Students in Analytical Chemistry Instrument - Varisky Abraham Dumanaw; Surjani Wonorahardjo; Hayuni Retno Widarti (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2020)
This study aims to determine differences in cognitive knowledge of students who are taught with a problem based learning aided by blended learning on the material of the uv-vis spectroscopy. This study uses a cognitive knowledge test instrument that has content validation of 87,92% with very good criteria and a Cronbach Alpha reliability coefficient of 0.653 in the high category. The research was conducted at the Universitas Negeri Manado in two classes. The experimental class was taught by the problem based learning model assisted by blended learning and the control class that was taught with a problem based learning model. The results showed a statistically significant difference in students' cognitive knowledge in both study classes (α = 0.050).